Phytoplankton dynamics under ice-cover in a subalpine lake - Spaulding, Sarah A., author; Ward, J. V., advisor; Baron, Jill, committee member; Moore, Janice, committee member (Colorado State University. Libraries, 1991)
The temporal dynamics of phytoplankton, as well as factors potentially controlling the dynamics, were examined in The Loch, a subalpine lake (3110 m above sea level) in Rocky Mountain National Park over the winter seasons of 1987-88 and 1988-89. The Loch (area = 4.98 ha, Zm = 4.7 m) was ice covered from early November until early May. The lake was sampled twice monthly at three discrete depths for the duration of ice cover. The formation of ice resulted in freeze concentration of lake water. Because of The Loch's large surface area to volume ratio, between 40 and 80% of the lake volume became frozen. The exclusion of impurities as ice formed led to increased concentrations of dissolved constituents in the remaining lakewater. Although not all ions increased, pH, Ca, Na, K, SO4, and alkalinity showed a significant increase (P < 0.05). The increases may have had an enriching affect on algal growth. However, nutrient concentrations were not measurably increased. Phosphorus (as ortho-phosphate) remained below detection limits (3 - 6 μg 1-1), nor did nitrate increase significantly with freeze concentration. Conservative ions changed only slightly over the winter season and with depth in the water column. However, there were changes in nutrient concentrations. Nitrate fluctuated with no discernable pattern during the first year and showed a clear decline the second year. Nitrate values were high (0.044 to 1.240 mg 1-1) compared to other high elevation Colorado lakes, and concentrations were probably not limiting to the phytoplankton. Silica concentration ranged from 1.3 to 3.6 mg 1-1 and also had late winter minima. The decline was attributed to depletion by the diatom Asterione/la formosa Hass.. Values for pH ranged between 5.8 and 6.7 but did not show any trends over the season. Alkalinity ranged from 28 to 165 ?eq 1-1. Oxygen concentrations were between 2.2 mg 1-1 and 10 mg 1-1 and varied over the season and with depth in the water column. Light impinging on the lake surface was at a minimum in January due to low aspect of the sun and shading of the lake by high ridges in the watershed. A low percentage of incident light transmitted through the ice surface was attributed more to low aspect of the sun, than ice thickness or snow accumulation. Light transmitted through the ice was rarely greater than 10 % of incident radiation. The winter zooplankton assemblage was composed nearly exclusively of cyclopoid copepods and rotifers. The copepods (Eucyclops agilis Koch and Acanthocyclops sp.). were low in number, with maximum densities of 6 organisms 1-1. The rotifers (Keratella hiemalis (Carlin), Notholca squamula (O.F. Müller) and Polyarthra sp.) reached greater abundances, the latter attaining maximum values of 700 organisms 1-1. The pattern of phytoplankton biomass during ice cover was consistent between the two years. The pattern was characterized by an early winter peak, followed by a minimum in January. A second maximum occurred in February / March, followed by a decrease until late May / April, and then a slight increase in May, when the ice melted. The pattern of algal biomass, and it resulted principally from the contribution of A. formosa. The dominant phytoplankton species in terms of biomass were A. formosa, Dinobryon sertu/aria Ehrenb., Cryptomonas ovata Ehrenb., and Peridinium cinctum (Müll.) Ehrenb.. Dominant species collectively contributed from 10 to 90 % of the total cells. Algal composition changed throughout the season and individual species varied in abundance with depth. Although the same dominant (and most of the rare) taxa were present in both years, they varied in time of occurrence and abundance. Chlorophytes, cryptophytes, and cyanobacteria were all important components of the phytoplankton, but they did not occur at the same time in both seasons.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Freshwater phytoplankton; Phytoplankton; Ice on rivers, lakes, etc.